What Factors Determine Banking Profitability In Indonesia During The Covid-19 Pandemic? - Abdul Rohman; Ahmad Nurkhin (Universitas Negeri Semarang, 2022)
Purpose : The banking industry faced significant challenges during the COVID-19 pandemic. Banking performance is being scrutinized for interested parties to evaluate future business projections. The purpose of this study is to analysis the profitability of Indonesian banks during the COVID-19 pandemic and to investigate what factors influence the profitability. Method : This research is quantitative research and uses panel data. The research sample is a banking company listed on the Indonesia Stock Exchange with a two-year observation period (2020-2021), that is, during the COVID-19 pandemic. There are 49 banks and unbalanced panel data obtained from 97-unit analysis. Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin are all used to measure banking profitability (NIM). The documentation method was used to collect data. The data was analyzed using descriptive statistics and multiple regression analysis with random effect model. Findings : The result indicate that only NPL has a significant negative effect on ROA and ROE, according to the findings. Meanwhile, even though it is negative, CAR has a significant impact on ROA and ROE. The effects of size and liquidity on ROA and ROE were not significant. Similarly, there is no significant evidence of size, liquidity, CAR, or NPL on the Indonesian banking NIM. It can be concluded that only NPL and CAR have a significant impact on Indonesian banking profitability. Novelty : The novelty in this paper is an analysis of banking profitability in Indonesia during the COVID-19 pandemic (2020-2021) and a study of the factors that influence it. Unbalanced data panel regression with random effect model was used to analyze the data. Keywords : Profitability; Return on Assets; Return on Equity; Net Interest Margin; Non-Performing Loan